MIGRATION AND CORONACRISIS: CONSEQUENCES, PROSPECTS, DIRECTIONS OF RESPONSE - Olena Malynovska (Стратегічна панорама, 2021)
Labor migration abroad has a significant impact on the socio-economic and demographic development of Ukraine. Therefore, awareness of the consequences of the pandemic for migration processes, taking into account the migration component in developing a strategy for overcoming the crisis is extremely important. The article focuses on finding the key answers to adequately respond to migration challenges. The question is: ‘How does the crisis affect the situation of migrants? How does the crisis affect the intensity and direction of migration flows? How will these changes affect the development of the Ukrainian economy and society?’ There is not enough data on the dynamics of modern international migration. Therefore, the review of the hypothetical migration situation, as well as the development of recommendations for possible policy solutions, are based not only on their analysis, but also on generalizing the effects of previous economic crises on migration processes, identification and extrapolation to modern realities of their essential characteristics.